Alcoholism, Fibroblast Growth Factor 23 and Cardiovascular Risk - Emilio González-Reimers; Geraldine Quintero-Platt; Candelaria Martín- González; Lucía Romero-Acevedo; Daniel Martínez-Martínez; Melchor Rodríguez-Gaspar; Francisco Santolaria-Fernández (Archives of Clinical Hypertension - Peertechz Publications, 2017)
Background: Bone metabolism is tightly regulated by several hormones that are synthesized in bone cells and that have effects not only on bone but on several distant organs. These hormones are involved in intermediate metabolism and modulate fatty acid transport, playing a role in insulin resistance, liver steatosis, atherosclerosis and cardiovascular risk. Aims: We review the association of fi broblast growth factor-23 (FGF-23) and α-Klotho with ardiovascular risk, especially in the alcoholic patient. Results: High levels of FGF-23 are associated with vascular risk, especially with vascular calcifi cations, hypertension, or left ventricular hypertrophy. Main Findings: Hyperphosphatemia constitutes a major stimulus for FGF-23 secretion, together with infl ammation and reduced iron availability, either by iron defi ciency or by iron sequestration in infl ammatory diseases. FGF-23 can be expressed by the damaged liver. Alcoholism is a proinfl ammatory condition, and in alcoholics there is an increased cardiovascular risk. Preliminary data suggest that FGF- 23 is raised in alcoholics. Conclusion: Increased FGF-23 levels have been described in association with hypertension, arterial wall calcifi cation, left ventricular hypertrophy and increased cardiovascular mortality, both in patients with or without chronic kidney disease. Some data suggest that FGF-23 is also related to increased vascular risk in alcoholics. Brief Summary FGF-23 is an osteocyte derived molecule related to cardiovascular risk. Hyperphosphatemia is a major trigger mechanism for its secretion, but infl ammatory conditions are also associated with increased FGF-23 production. Some data suggest that FGF-23 may be also related with the increased vascular risk observed in chronic alcoholic patients.